DEGRADATION STUDIES OF METHYLDIETHANOLAMINE BY USING UV/H202 ADVANCED OXIDATION PROCESS - HARIMURTI, SABTANTI (2013)
Methyldiethanolamine (MDEA) in aqueous solutions is frequently used for scrubbing carbon dioxide (C02) and hydrogen sulfide (HzS) from natural gas. Large quantity of MDEA disposed into the wastewater during cleaning and maintenance as well as shutdown of the absorption and desorption columns of the gas processing plant. The MDEA is not readily biodegradable and such wastewater cannot be treated using the conventional treatment facility. Advanced Oxidation Processes (AOP's), such as oxidation by Fenton's reagent, UV/Hz02 and UV/Ozone have been recommended as a class of techniques used for the total/partial degradation of recalcitrant organics which are not readily amenable to conventional biological oxidation. Based on the advantages of UV/H20z process such as no formation of sludge during the treatment, applicable for a wide range of pH, and high capability of hydroxyl radical production, the UV /H20 2 process was chosen for the treatment of effluents containing MDEA from refinery plant. For this purpose, a synthetic MDEA solution and a real effluent from gas processing unit of a refinery were used for the experiments employing UV/H20 2 advanced oxidation process. The degradation of MDEA was found to be highly dependent on the initial concentration of H20 2, the initial pH, and the reaction temperature. The important parameters that govern the MDEA degradation by UV/Hz02 process were optimized using response surface methodology (RSM). The optimum conditions for degradation process of synthetic MDEA waste were at initial pH = 9.76, ratio between contaminant to oxidant = 1000 ppm of organic carbon to 0.22 M H20 2 , and temperature = 30°C. Whilst the optimum condition of degradation process of real refinery effluent was at initial pH= 8.13, ratio between contaminant to oxidant= 1000 ppm organic carbon to 0.24 M of H20 2 , and temperature= 30°C.